Chemical and morphological evolution of copper nanoparticles obtained by pulsed laser ablation in liquid - Goncharova, Darya A.; Kharlamova, Tamara S.; Lapin, Ivan N.; Svetlichnyi, Valerii A. (The Journal of Physical Chemistry C)
Pulsed laser ablation in liquid (PLAL) is a promising method to prepare copper/copper oxide nanoparticles (NPs), with the liquid used being an important factor to control their properties. The roles of the species dissolved in the liquid in the course of NP formation during the PLAL as well as the effects of organic solvents in the stabilization of the colloids obtained remain a debate. The peculiarities of the formation and alteration of the particles in ethyl alcohol as well as the effect of low amounts of oxidizing and acid-base species on the composition, structure, morphology, and stability of the NPs in the water colloids are examined. The observed high resistance of Cu NPs toward deep oxidation in ethyl alcohol suspension is shown to be connected with a competitive adsorption mechanism rather than the formation of the carbon shell. Pulsed laser ablation (PLA) of copper in distilled water yields cubic Cu2O NPs, while low amounts of NaOH and H2O2 species change the transformation route of copper NPs in the colloids formed. In the case of H2O2, the primary formation of the sheetlike and flowerlike Cu(OH)2 particles occurs in the course of PLA followed by their pseudomorphous transformation into CuO particles during the suspension aging. The presence of NaOH yields leaflike CuO mesostructures via the tetrahydroxocuprate anion mechanism. On the basis of the results obtained, the schemes for the formation of the particles are proposed. Copyright @ 2019 American Chemical Society.